Educational needs assessment of faculty members in Ardabil University of Medical Sciences - Y., Shafaei-Khanghah; A., Enteshari-Moghaddam; F., Nasl Seraji; F., Amani; H., Ghobadi; E., Farzaneh (International Journal Of Community Medicine And Public Health, 2017)
Background: Identifying the educational needs is an essential step in planning faculty development programs and plays an important role in promoting the quality of education and can help educational planners to be able to design effective strategies based on available resources and provide effective training. The aim of this study was to determine the educational needs of faculty members in medical school of Ardabil University of Medical Sciences. Methods: This is a descriptive cross-sectional study that has been done on 88 faculty academic members in two clinical and basic groups Data collected by a questionnaire and collected data were analyzed using statistical methods in SPSS.20. Results: 53.4% of cases were in group clinical and rests of them were in basic group. 75% of cases were male and rest of them were female. 57% had more than 10 years of work experience. There was a significant difference between two groups in the field of research in the area ethics in research and in the field of information technology in the area of using electronic resources between two groups. Based on the prioritization of the needs within the clinical and basic academic members, the greatest need in both groups was related to the writing of scientific texts in English. Also, the lowest priorities within the clinical and basic members were the familiarity with English journals (26.8%) and the use of electronic resources (27.7%). Conclusions: Results showed that the level and type of needs among university faculty members fits with the needs of the faculty members in other universities that is required to response the needs of clinical and basic professors, necessary educational and research actions based on the priorities in 6 areas will happen in future.